Poetyckie kartki z łagru — codzienność i tęsknoty (o poezji Łarysy Marozawej) - Cupała, Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This article deals with poems of a Belarusian poet, Larysa Marozawa. Marozawa was one of the victims of Stalin's regime. The author puts forward the thesis that in Belarus today the same methods are used to eliminate political opposition as sixty years ago. The paper presents examples of modern political prisoners in Belarus. Next, the author analyzes several surviving works of Larysa Marozawa. The author is trying to prove that the atmosphere described in these poems may correspond with what is happening today in the labor camps in Belarus.